Spectroscopic Characteristics of Dissolved Organic Matter in Afforestation Forest Soil of Miyun District, Beijing - Shi-Jie Gao; Chen Zhao; Zong-Hai Shi; Jun Zhong; Jian-Guo Liu; Jun-Qing Li (Journal of Analytical Methods in Chemistry)
In this study, soil samples collected from different plain afforestation time (1 year, 4 years, 10 years, 15 years, and 20 years) in Miyun were characterized, including total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), available K (K+), microbial biomass carbon (MBC), and dissolved organic carbon (DOC). The DOM in the soil samples with different afforestation time was further characterized via DOC, UV-Visible spectroscopy, excitation-emission matrix (EEM) fluorescence spectroscopy, and 1H NMR spectroscopy. The results suggested that the texture of soil sample was sandy. The extracted DOM from soil consisted mainly of aliphatic chains and only a minor aromatic component. It can be included that afforestation can improve the soil quality to some extent, which can be partly reflected from the indexes like TOC, TN, TP, K+, MBC, and DOC. And the characterization of DOM implied that UV humic-like substances were the major fluorophores components in the DOM of the soil samples, which consisted of aliphatic chains and aromatic components with carbonyl, carboxyl, and hydroxyl groups.